Prospective Association Between Leukocyte Telomere Length and Mortality: Findings from the Black Women’s Experiences Living with Lupus (BeWELL) Study - David H Chae; Connor D Martz; Amani M Nuru-Jeter; Tiffany Yip; Jue Lin; Eloisa Bonfá; Elissa S Epel; Kenneth Saag; Cristina Lanata; Sofia Nadgauda; Jesus Ramirez-Valles; Jinoos Yazdany (Clinical and Experimental Immunology, 2026)
Abstract Leukocyte telomere length (LTL) is a biomarker of replicative history of cells and has been posited to be an indicator of biological aging. LTL may yield insight into immunomodulatory disorders, including systemic lupus erythematosus (SLE), an immune-mediated inflammatory disease that disproportionately affects Black/African American women. This study examined the association between LTL and mortality among 422 Black/African American women in the Black Women’s Experiences Living with Lupus (BeWELL) Study. Participants were recruited from metropolitan Atlanta, Georgia between April 2015 and May 2017, and followed for a mean of 1.98 years (SD=0.38). LTL was measured as the telomere to single copy gene ratio (T/S). Mortality was assessed prospectively. Cox proportional hazards regression models adjusting for sociodemographic, health, and disease characteristics were specified. A total of 19 participants died during the follow-up period. Adjusting for demographic, socioeconomic, and health-related covariates, longer LTL was associated with lower risk of mortality (Hazard Ratio=0.13, 95% Confidence Interval=0.02, 0.83, P=0.03). This study is the first to report an association between LTL and subsequent mortality among Black/African American women with SLE. Findings may be particularly relevant for this population, which has been shown to experience severe disease consequences. Future research may further explore LTL in mechanistic studies of SLE and assess the utility of LTL for monitoring disease progression and outcomes.